Immunotherapy Summary for Cytokine Storm in COVID-19 - Li, Yaqun; Zhao, Wenjie; Liu, Jinhua; Chen, Zichao; Lv, Qingtao; Zhang, Zhen (Frontiers in Pharmacology, 2021)
COVID-19 pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has ravaged the world, resulting in an alarming number of infections and deaths, and the number continues to increase. The pathogenesis caused by the novel coronavirus was found to be a disruption of the pro-inflammatory/anti-inflammatory response. Due to the lack of effective treatments, different strategies and treatment methods are still being researched, with the use of vaccines to make the body immune becoming the most effective means of prevention. Antiviral drugs and respiratory support are often used clinically as needed, but are not yet sufficient to alleviate the cytokine storm (CS) and systemic inflammatory response syndrome. How to neutralize the cytokine storm and inhibit excessive immune cell activation becomes the key to treating neocoronavirus pneumonia. Immunotherapy through the application of hormones and monoclonal antibodies can alleviate the immune imbalance, but the clinical effectiveness and side effects remain controversial. This article reviews the pathogenesis of neocoronavirus pneumonia and discusses the immunomodulatory therapies currently applied to COVID-19. We aim to give some conceptual thought to the prevention and immunotherapy of neocoronavirus pneumonia.